2016
DOI: 10.3390/nu8120757
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Fructose Intake Affects Transcriptome Changes and Programmed Hypertension in Offspring in Later Life

Abstract: Hypertension originates from early-life insults by so-called “developmental origins of health and disease” (DOHaD). Studies performed in the previous few decades indicate that fructose consumption is associated with an increase in hypertension rate. It is emerging field that tends to unfold the nutrient–gene interactions of maternal high-fructose (HF) intake on the offspring which links renal programming to programmed hypertension. Reprogramming interventions counteract disturbed nutrient–gene interactions ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…To our knowledge, this is the first study to examine the potential benefit of maternal supplementation with acetate or 3,3‐dimethyl‐1‐butanol in HFD‐induced programed hypertension. Consumption of various degrees of HFD ranging from 10% to 60% by pregnant dams have been reported to cause hypertension in their adult offspring . Consistent with previous reports, we found that maternal HFD produced elevation of BP in 12‐week‐old male offspring.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, this is the first study to examine the potential benefit of maternal supplementation with acetate or 3,3‐dimethyl‐1‐butanol in HFD‐induced programed hypertension. Consumption of various degrees of HFD ranging from 10% to 60% by pregnant dams have been reported to cause hypertension in their adult offspring . Consistent with previous reports, we found that maternal HFD produced elevation of BP in 12‐week‐old male offspring.…”
Section: Discussionsupporting
confidence: 91%
“…BP was measured in conscious rats on week 3, 4, 8, and 12 using an indirect tail‐cuff method (BP‐2000, Visitech Systems, Inc., Apex, NC, USA), as described previously . To ensure accuracy and reproducibility, the rats were allowed to adapt to restraint and tail‐cuff inflation for 1 week prior to the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike glucose, which is metabolized widely in the body, fructose is converted into glucose, glycogen, lactate, and fatty acids mainly in the liver [8] . Since fructose can be transported and produced by the placenta [9] , [10] , it is considered that the fetal programming process is driven not only by fructose but also by its metabolites [11] .…”
Section: Metabolic Effects Of Fructose On Metabolic Syndromementioning
confidence: 99%
“…9 Maternal programming with a high-fructose diet (HFR) has many effects on offspring, including hypertriglyceridemia, hypertension, hyperinsulinemia and liver fat infiltrates. 10,11 However, little is known about the effects on the offspring of a high-fructose diet consumed by the father or both the mother and father. The present study aimed to evaluate the effects of a high-fructose diet consumed by the mother, by the father and by both the mother and father on the metabolism and liver health of adult male offspring, including the β-oxidation, lipogenesis and inflammation pathways.…”
Section: Introductionmentioning
confidence: 99%